E-learning - Enstroem, Rickard; Bhawna, Bhawna (My University, 2026)
E-learning leverages digital technologies and learning platforms to deliver educational content that is flexible, scalable, accessible, and interactive. In higher education, it supports several delivery modalities, including online, hybrid, and face-to-face formats. This chapter examines the theoretical principles underpinning e-learning, its foundational design components, and its role in supporting learner engagement and personalization. It highlights persistent challenges like digital equity and academic integrity and explores emerging trends, including artificial intelligence and immersive technologies. The chapter addresses these themes and provides insights into how e-learning reshapes higher education to meet evolving pedagogical needs.
Keywords: blended learning; digital learning; distance learning; educational technology; e-learning; instructional design; interactive learning; learning analytics; learning management system; mobile learning; online education; student engagement; virtual classrooms